Interactions of pyrethroids with the voltage-gated sodium channel - Atkinson, Susan (2003)
Pyrethroid insecticides act on the voltage-gated sodium channel and mutations of the channel can confer resistance in many insect species. For example, the kdr (LI014F) mutation found in domain IIS6 and the super-kdr (M918T) mutation found in the IIS4-S5 linker of the insect Drosophila melanogaster para sodium channel reduces the sensitivity of the channel to pyrethroids.